Prevalensi Bakteri Staphylococcus aureus Pada Pakaian Bekas di Pasar Panorama Bengkulu - Abdul Rahman Singkam; Mustika Elmi Dayana; Fenty Agustin; Mia Auliani; Avrilia Zurli; Agrezia Rahmanda; Tiara Fadillah (Universitas PGRI Silampari, 2024)
The aim of this research is to determine the existence of Staphylococcus bacteria in second hand clothes at Pasar Panorama Bengkulu. This research used an observational method by counting the population of Staphylococcus bacteria in various types of second hand clothes. The collected clothes were diluted and the staphylococcus were isolated by using nutrient agar as a growth media. The results of this research showed that there were bacterial colonies produced from second clothes with the highest number of colonies on cotton clothes, 35 X 103. The research is expected to have a contribution as a consideration for the community when buying second clothes and build public awareness to prevent transmission of the disease caused by them.